Functions of the press: Organizations´ study - Local councils and authorities - Weibull, Lennart; Aldemark, Lars (University of Gothenburg, 1982)
This study is part of the research programme The Role of the Press in Society, a project initiated by the 1972 Commission of tbe Press. The starting point for the research programme was the situation in the Swedish press at the beginning of 1970ies. At the time the newspaper market in Sweden seemed to be at some sort of changing point. The party press structure had been broken up by the concentration process on the newspaper market. On the other hand new types of newspaper were expanding. At the same time millions of SEK went to the newspaper industry from the government. For many newspapers this money seemed to be the only way of keeping alive. At this point the question put by the 1972 Commission of the Press was: how meaningful are those subsidies? According to which principles shall subsidies be given? To answer these questions other questions had to be asked: Which role do newspaper play in the Swedish society of today? Which significance do they have for the work of a democratic political system? For the reporting of political news? For the public opinion formation?
The survey illustrates how organizations regard their relation to the local area, to the general public and members and which part various types of media play in the work of the organization. Further some questions were put about which role the daily press should have in political life.

This study is part of the research programme The Role of the Press in Society, a project initiated by the 1972 Commission of tbe Press. The starting point for the research programme was the situation in the Swedish press at the beginning of 1970ies. At the time the newspaper market in Sweden seemed to be at some sort of changing point. The party press structure had been broken up by the concentration process on the newspaper market. On the other hand new types of newspaper were expanding. At the same time millions of SEK went to the newspaper industry from the government. For many newspapers this money seemed to be the only way of keeping alive. At this point the question put by the 1972 Commission of the Press was: how meaningful are those subsidies? According to which principles shall subsidies be given? To answer these questions other questions had to be asked: Which role do newspaper play in the Swedish society of today? Which significance do they have for the work of a democratic political system? For the reporting of political news? For the public opinion formation?
The survey illustrates how organizations regard their relation to the local area, to the general public and members and which part various types of media play in the work of the organization. Further some questions were put about which role the daily press should have in political life.
Pressens funktioner: Organisationsstudien - Kommunala nämnder och myndigheter
Keywords: Media; Media; Social Sciences; Samhällsvetenskap